Joseph Smith, Jr. reappraisals after two centuries - Neilson, Reid Larkin, 1972-; Givens, Terryl (Oxford ; New York : Oxford University Press, 2009)
Mormon founder Joseph Smith is one of the most controversial figures of 19th century American history, and a virtually inexhaustible subject for analysis. In this volume, 15 scholars offer essays on how to interpret and understand Smith and his legacy.
Prophets in America circa 1830 : Ralph Waldo Emerson, Nat Turner, Joseph Smith / Richard H. Brodhead -- Joseph Smith, American culture, and the origins of Mormonism / Klaus J. Hansen -- "I love all men who dive" : Herman Melville and Joseph Smith / Richard Dilworth Rust -- The metaphysical Joseph Smith / Catherine L. Albanese -- Joseph Smith vs. John C. Calhoun : the state's rights dilemma and early Mormon history / James B. Allen -- Joseph Smith and creation of the sacred / Richard Lyman Bushman -- Joseph Smith : prophecy, process, and plenitude / Terryl L. Givens -- Visions, revelations, and courage in Joseph Smith / Douglas J. Davies -- Seeking the face of the Lord : Joseph Smith and the first temple tradition / Margaret Barker and Kevin Christensen -- Tracking the sincere believer : "authentic" religion and the enduring legacy of Joseph Smith Jr. / Laurie F. Maffly-Kipp -- The possibility of Joseph Smith : some evangelical probings / Richard J. Mouw -- The prophethood of Joseph Smith / Wayne Hudson -- Joseph Smith and nineteenth-century Mormon mappings of Asian religions / Reid L. Neilson -- Studying Joseph Smith Jr. : a guide to the sources / David J. Whittaker.
Includes bibliographical references (p. [239]-270) and index.
Description based on print version record.
Keywords: Smith, Joseph, -- 1805-1844.; RELIGION -- Christianity -- Church of Jesus Christ of Latter-day Saints (Mormon); Electronic books